Multilingualism in Limassol LUCIDE city report - Papadima-Sophocleous, Salomi; Nicolaou, Anna; Boglou, Dimitrios; Parmaxi, Antigoni (My University, 2015)
The purpose of this report is to provide an overview of the current situation of multilingualism in the city of Limassol and to explore issues pertaining to multilingualism and plurilingualism in various spheres and aspects of the city life. It is part of the work carried out by The LUCIDE network (Languages in Urban Communities: Integration and Diversity for Europe), which is composed of university and civic partners from thirteen European countries and other research teams in other parts of the world. LUCIDE’s aims are to build up a picture of how communication occurs in multilingual settings across the EU and beyond, depict how communication occurs in multilingual cities and develop ideas about how to manage multilingual citizen communities. Through an examination of Limassol’s history of language diversity, as well as through an analysis of the city from a contemporary point of you, the report will attempt to portray the multilingual Limassol of yesterday and of today. In addition, the report will examine certain research questions, such as good practice in language learning for immigrants, the role of linguistic support in social inclusion, provision for communication and cultural exchange with neighbouring languages, promotion of intercultural dialogue, and the changing face of migration in our civic context. The document will also address more specific research questions such as language visibility and invisibility, affordances at the level of governance or policy, as well as challenges and obstacles involved in creating and managing multilingualism in the city of Limassol. Findings demonstrate several aspects of multilingualism, such as how communication is achieved among the citizens, how the city encourages multilingualism, as well as what policies and practices are implemented in order to promote intercultural dialogue and mutual understanding. As a result of the findings, suggestions for best practices, introduction or improvement of policies and visions of the city are put forward.
Keywords: City Report; Cyprus; Multilingualism